Clinical and Epidemiological Aspects of Leptospirosis Patients in Cienfuegos. 2001 - 2010 - Lourdes Elena Duany Badell; Madeline Achón García; Alfredo Varen Álvarez; Elena Badell Taquechel; Nicolás Felipe Morales Pérez; Tania Bolaños Valladares (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: leptospirosis has been historically considered the major zoonotic disease worldwide, which holds true for the municipality and province of Cienfuegos. Objective: to characterize patients with leptospirosis clinically and epidemiologically. Methods: a descriptive, retrospective study was conducted in 83 patients with leptospirosis reported in the municipality of Cienfuegos from 2001-2010. Variables analyzed included: age, sex, risk group, time of exposure to risk tasks, use of protective equipment, immunization, chemoprophylaxis, signs and symptoms and serology. Results: a rate of 76,0 per 100 000 inhabitants was obtained for males; 55.4% were agricultural workers. Seventy four point five percent of temporarily exposed patients improperly used the protective equipment. Seventy eight point one percent of those diagnosed and constantly exposed to risk was not immunized and only 9.8% of the patients temporarily exposed to risk received chemoprophylaxis. Fever and headache were the symptoms developed in all cases. Conclusion: using personal protection at work decreased the likelihood of contracting this disease. Predominant symptoms were fever and headache; the increase in morbidity coincided with the last two quarters of the year, which are the main harvest seasons.